A Rendezvous Protocol with the Heterogeneous Spectrum Availability Analysis for Cognitive Radio Ad Hoc Networks. (31st January 2013) - Romaszko, Sylwia
Abstract : In cognitive radio ad hoc networks, a frequently changing environment, varying channel occupancy statistics, and heterogeneous spectrum availability result in a need to meet on a common channel and to initiate a communication. This process of two or more CRs, meeting each other in the same channel, is called a rendezvous (RDV). RDV is essential for establishment of a communication link. Hence, methods guaranteeing that all nodes meet periodically in reasonable periods of time should be developed. In this study, we evaluate a torus Quorum System (QS) and Difference Set (DS) based rendezvous protocol in an asymmetric channel view case (heterogeneous channel availability). Regardless of the diversity of channels of CRs the protocol guarantees RDV on either all channels or almost all channels. Furthermore, the nodes meet multiple times on different channels in a period, which increases the chance of successful establishment of a communication link.